Comparison among major codes for the stability design of steel compression members in steel bridges with the partial factors taken into consideration. (August 2021) - Chen, Xiang; Nakamura, Shozo; Kishi, Yusuke; Ikezue, Kazutaka; Mizuguchi, Toshiki; Hirayama, Hiroshi
Abstract: Provisions aimed at stability design have been drawn up by various countries according to many previous researches and their own practice. However, calculated results based on different codes greatly differ. Stability design for the steel compression members of steel bridges in four codes adopting the partial factor design method were outlined and comparatively analysed in this study. Calculation methods following the codes of four countries were detailed in the case of the steel box section column. The nominal strengths related to the normalized slenderness and width-thickness ratios were discussed and compared with FEA results. It is found that results following EC3 correspond with the FEA results better than other codes. The safety factors were calculated and compared with each other. In addition, the design strength and allowable strength among these codes were discussed. The results indicate that EC3 and AASHTO provide relatively high allowable strength for the compressive steel box section columns in general while JTG D64 and JRA give conservative results.